GRADUATE STUDENTS’ MOTIVATION REGULATION STRATEGIES IN FACING ACADEMIC WRITING AMID COVID-19 PANDEMIC - Wijaya, Kristian Florensio; Setiawan, Niko Albert (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
Abstract To be more proficient and self-regulated, L2 academic writers, the deployment of motivation regulation strategies should be incorporated at the commencement of academic writing learning enterprises, particularly during this pandemic situation. According to previous studies, the establishment of robust motivation regulation strategies will potentially help L2 academic writers to better manage the ongoing writing learning dynamics and cope with varied upcoming challenges. Specifically, this study was conducted qualitatively by lending support from qualitative content analysis in order to offer more overarching findings derived from actual events experienced by the participants. To comply with this objectivity, two research instruments were also utilized in this study namely the Likert-Scale questionnaire and open-ended interviews. Further, the Likert-Scale questionnaire was administered via Google Forms to be filled out by 36 English education master students from batch 2018 and 2019, and the open-ended interview inquiries were sent through WhatsApp application in order to obtain the responses from the three random selected interviewees. Results from this study revealed that the majority of English education master students had successfully become more competent and resilient academic writers through five major streams of motivation regulation strategies namely interest enhancement, performance self-talk, mastery self-talk, self-consequating, and environmental structuring. Keywords: Motivation regulation strategies, academic writing, graduate students, Covid-19 pandemic